2016
DOI: 10.1016/j.pmrj.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Latent Trigger Points in Lower Limb Muscles in Asymptomatic Subjects

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 41 publications
0
17
1
2
Order By: Relevance
“…The PPT in the present study were higher than those of Cerezo-T ellez et al 2016, who treated active TrPs, but lower than the PPT reported in TrPs in the quadriceps muscles of patients with post-meniscectomy pain (Torres-Chica et al, 2014). However, the PPT was comparable to those reported by Zuil-Escobar et al (2016) who measured the PPT of latent TrPs in the legs.…”
Section: Discussioncontrasting
confidence: 65%
“…The PPT in the present study were higher than those of Cerezo-T ellez et al 2016, who treated active TrPs, but lower than the PPT reported in TrPs in the quadriceps muscles of patients with post-meniscectomy pain (Torres-Chica et al, 2014). However, the PPT was comparable to those reported by Zuil-Escobar et al (2016) who measured the PPT of latent TrPs in the legs.…”
Section: Discussioncontrasting
confidence: 65%
“…[20][21][22][23] Moreover, female predisposition to the asymptomatic form of MPS in the lower limbs has been confirmed. 24 Thus, one has to assume that nociplastic pain may result from the response to a prolonged LBLP or can develop due to mechanical posture overloading or muscle involvement during the acute phase of disc disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to reduce location-specific variance, the search, performed by a trained investigator, was restricted to the area of TrP2 according to Travell and Simons [20], which is located near the muscle belly. The gastrocnemius muscle was chosen because a) it has been shown to exhibit the highest prevalence of latent MTrP in healthy subjects [21], and b) foam rolling is most feasible and easy to standardize at the lower extremity.…”
Section: Methodsmentioning
confidence: 99%